2021
DOI: 10.1111/ner.13222
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Outcomes After Dorsal Root Ganglion Stimulation in the Treatment of Neuropathic Pain After Peripheral Nerve Injury of Upper and Lower Extremities

Abstract: Objectives Traumatic peripheral nerve injuries (PNI) often result in severe neuropathic pain which typically becomes chronic, is recalcitrant to common analgesics, and is associated with sleep disturbances, anxiety, and depression. Pharmacological treatments proven to be effective against neuropathic pain are not well tolerated due to side effects. Neuromodulative interventions such as peripheral nerve or spinal cord stimulation have generated mixed results and may be limited by reduced somatotopic specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Our study was set up to present pooled data up to one‐year post‐permanent implant as this is the most common follow‐up period in published literature. The field is moving toward collecting longer term outcomes as exemplified by recent congress presentations . These independent studies support effective pain relief and quality of life improvements up to three years post‐implant.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was set up to present pooled data up to one‐year post‐permanent implant as this is the most common follow‐up period in published literature. The field is moving toward collecting longer term outcomes as exemplified by recent congress presentations . These independent studies support effective pain relief and quality of life improvements up to three years post‐implant.…”
Section: Discussionmentioning
confidence: 99%
“…Pain syndrome etiology for these reports varied widely which included phantom limb pain, post‐Lyme disease peripheral neuropathic pain, anterior cutaneous nerve entrapment, postsurgical knee pain, neuropathic pain after peripheral nerve injury, diabetic peripheral neuropathy, refractory loin pain hematuria syndrome, and idiopathic small fiber neuropathy of the left foot. Eight out of nine patients reports (19,20,31,34,35,41–43) demonstrated 50% or greater pain relief, post‐trial period, when observed at the time of last follow‐up. In this group, (18/65) patients experienced complications including: lead dislocation (one requiring explant (43)), lead breakage, device pocket pain, device overstimulation, lead migration, and superficial wound infection.…”
Section: Resultsmentioning
confidence: 98%
“…There is early and limited evidence that suggests that DRGS may prove to be a beneficial salvage strategy in patients that lose SCS efficacy in the long term (15,16). In our review, we found: (10/28) mentioned failed conventional management without detailed description of specific treatments (17–25), (7/28) failed to mention the failure of early management (26–32), (3/28) reported patients failing pharmacological management only (33–35), and (9/28) detail specific failed early management therapies prior to DRGS treatment (25,36–43). Of these nine reports, (5/9) detailed the failure of SCS previous with (4/5) detailing patients specifically.…”
Section: Resultsmentioning
confidence: 99%
“…It must be considered that with the passage of time, increased experience reduces the rate of complications. [46,47].…”
Section: Resultsmentioning
confidence: 99%